Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the matrix equation [tex]\(-M + KX = J\)[/tex], we need to find the matrix [tex]\(X\)[/tex].
Given:
[tex]\[ M = \begin{pmatrix} -4 & 0 \\ 4 & -1 \end{pmatrix}, \quad K = \begin{pmatrix} 1 & 3 \\ 4 & 3 \end{pmatrix}, \quad J = \begin{pmatrix} 13 & 12 \\ 23 & 13 \end{pmatrix} \][/tex]
First, we'll rewrite the equation in a more convenient form. We have:
[tex]\[ -M + KX = J \][/tex]
Rearrange to isolate [tex]\(KX\)[/tex]:
[tex]\[ KX = J + M \][/tex]
Now, calculate [tex]\(J + M\)[/tex], the sum of the matrices [tex]\(J\)[/tex] and [tex]\(M\)[/tex]:
[tex]\[ J + M = \begin{pmatrix} 13 & 12 \\ 23 & 13 \end{pmatrix} + \begin{pmatrix} -4 & 0 \\ 4 & -1 \end{pmatrix} = \begin{pmatrix} 13 + (-4) & 12 + 0 \\ 23 + 4 & 13 + (-1) \end{pmatrix} = \begin{pmatrix} 9 & 12 \\ 27 & 12 \end{pmatrix} \][/tex]
Next, we need to solve for [tex]\(X\)[/tex] by isolating it. To do that, we need the inverse of matrix [tex]\(K\)[/tex]. The inverse [tex]\(K^{-1}\)[/tex] satisfies:
[tex]\[ KK^{-1} = I \][/tex]
The inverse of a 2x2 matrix [tex]\(K = \begin{pmatrix} a & b \\ c & d \end{pmatrix}\)[/tex] is given by:
[tex]\[ K^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For our matrix [tex]\(K\)[/tex]:
[tex]\[ K = \begin{pmatrix} 1 & 3 \\ 4 & 3 \end{pmatrix} \][/tex]
where [tex]\(a = 1\)[/tex], [tex]\(b = 3\)[/tex], [tex]\(c = 4\)[/tex], and [tex]\(d = 3\)[/tex]. Now calculate the determinant:
[tex]\[ \det(K) = ad - bc = (1)(3) - (3)(4) = 3 - 12 = -9 \][/tex]
Thus, the inverse [tex]\(K^{-1}\)[/tex] is:
[tex]\[ K^{-1} = \frac{1}{-9} \begin{pmatrix} 3 & -3 \\ -4 & 1 \end{pmatrix} = \begin{pmatrix} -0.3333 & 0.3333 \\ 0.4444 & -0.1111 \end{pmatrix} \][/tex]
With [tex]\(K^{-1}\)[/tex] calculated, we can now solve for [tex]\(X\)[/tex]:
[tex]\[ X = K^{-1}(J + M) \][/tex]
Perform the matrix multiplication:
[tex]\[ X = \begin{pmatrix} -0.3333 & 0.3333 \\ 0.4444 & -0.1111 \end{pmatrix} \times \begin{pmatrix} 9 & 12 \\ 27 & 12 \end{pmatrix} = \begin{pmatrix} 6 & 0 \\ 1 & 4 \end{pmatrix} \][/tex]
Thus, the solution for the equation [tex]\(-M + KX = J\)[/tex] is:
[tex]\[ X= \begin{pmatrix} 6 & 0 \\ 1 & 4 \end{pmatrix} \][/tex]
Given:
[tex]\[ M = \begin{pmatrix} -4 & 0 \\ 4 & -1 \end{pmatrix}, \quad K = \begin{pmatrix} 1 & 3 \\ 4 & 3 \end{pmatrix}, \quad J = \begin{pmatrix} 13 & 12 \\ 23 & 13 \end{pmatrix} \][/tex]
First, we'll rewrite the equation in a more convenient form. We have:
[tex]\[ -M + KX = J \][/tex]
Rearrange to isolate [tex]\(KX\)[/tex]:
[tex]\[ KX = J + M \][/tex]
Now, calculate [tex]\(J + M\)[/tex], the sum of the matrices [tex]\(J\)[/tex] and [tex]\(M\)[/tex]:
[tex]\[ J + M = \begin{pmatrix} 13 & 12 \\ 23 & 13 \end{pmatrix} + \begin{pmatrix} -4 & 0 \\ 4 & -1 \end{pmatrix} = \begin{pmatrix} 13 + (-4) & 12 + 0 \\ 23 + 4 & 13 + (-1) \end{pmatrix} = \begin{pmatrix} 9 & 12 \\ 27 & 12 \end{pmatrix} \][/tex]
Next, we need to solve for [tex]\(X\)[/tex] by isolating it. To do that, we need the inverse of matrix [tex]\(K\)[/tex]. The inverse [tex]\(K^{-1}\)[/tex] satisfies:
[tex]\[ KK^{-1} = I \][/tex]
The inverse of a 2x2 matrix [tex]\(K = \begin{pmatrix} a & b \\ c & d \end{pmatrix}\)[/tex] is given by:
[tex]\[ K^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For our matrix [tex]\(K\)[/tex]:
[tex]\[ K = \begin{pmatrix} 1 & 3 \\ 4 & 3 \end{pmatrix} \][/tex]
where [tex]\(a = 1\)[/tex], [tex]\(b = 3\)[/tex], [tex]\(c = 4\)[/tex], and [tex]\(d = 3\)[/tex]. Now calculate the determinant:
[tex]\[ \det(K) = ad - bc = (1)(3) - (3)(4) = 3 - 12 = -9 \][/tex]
Thus, the inverse [tex]\(K^{-1}\)[/tex] is:
[tex]\[ K^{-1} = \frac{1}{-9} \begin{pmatrix} 3 & -3 \\ -4 & 1 \end{pmatrix} = \begin{pmatrix} -0.3333 & 0.3333 \\ 0.4444 & -0.1111 \end{pmatrix} \][/tex]
With [tex]\(K^{-1}\)[/tex] calculated, we can now solve for [tex]\(X\)[/tex]:
[tex]\[ X = K^{-1}(J + M) \][/tex]
Perform the matrix multiplication:
[tex]\[ X = \begin{pmatrix} -0.3333 & 0.3333 \\ 0.4444 & -0.1111 \end{pmatrix} \times \begin{pmatrix} 9 & 12 \\ 27 & 12 \end{pmatrix} = \begin{pmatrix} 6 & 0 \\ 1 & 4 \end{pmatrix} \][/tex]
Thus, the solution for the equation [tex]\(-M + KX = J\)[/tex] is:
[tex]\[ X= \begin{pmatrix} 6 & 0 \\ 1 & 4 \end{pmatrix} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.